The Effect of The Company's Liquidity Ratio and Size on The Value of Agricultural Companies - Agus Darmawan; Yusuf Iskandar; Heliani (Nusantara Science and Technology Proceedings, 2020)
This analysis aims to examine the impact of liquidity and firm size on firm valuation by analyzing empirical evidence from firms that went public on the Indonesia Stock Exchange between 2015 and 2017. Between 2015 and 2017, the population for this study consisted of 22 firms that were classified on the Indonesian Stock Exchange. Purposive sampling was used to collect data. The sample parameters are as follows: (1) firms that have always presented earnings results annually between 2015 and 2017, and (2) companies that have continued to pay dividends annually between 2015 and 2017. The data is derived from articles on the IDX database, which can be accessed at www.idx.co.id. During the past four years, there have been 16 businesses sampled. The regression analysis methodology was used in this study. The findings indicate that firm liquidity has a favorable and statistically relevant impact on firm valuation. The scale of the company has a detrimental and marginal effect on the firm's value.